2013
DOI: 10.1210/jc.2013-2672
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Elastographic Strain Index and Thyroid Fine-Needle Aspiration Cytology in 631 Thyroid Nodules

Abstract: The elastographic SI has a high sensitivity, specificity, and negative predictive value for the diagnosis of thyroid malignancy both in the presence and in the absence of ATD. If our data on USE are also confirmed in THY3 nodules, FNAC could be avoided in a number of thyroid nodules with certain features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 32 publications
3
17
0
2
Order By: Relevance
“…A cutoff value >2.905 produced greater sensibility and negative predictive value than grey scale criteria [76].…”
Section: Limitations and Causes Of False Results For Srmentioning
confidence: 87%
“…A cutoff value >2.905 produced greater sensibility and negative predictive value than grey scale criteria [76].…”
Section: Limitations and Causes Of False Results For Srmentioning
confidence: 87%
“…In our previously published study, we reported that tissue stiffness measured by strain elastography is an independent predictor of TC (Azizi et al 2013). Several studies showed that this technology can play an important role in TN selection and risk assessment for malignancy before FNAB (Bhatia et al 2011;Friedrich-Rust et al 2013;Magri et al 2013;Rivo-V azquez et al 2013).…”
Section: Introductionmentioning
confidence: 92%
“…It is possible that our sample of 35 subjects was insufficiently large to show weak associations that exist; alternatively, given the mixed findings in the literature, it is possible that these findings are specific to particular patient cohorts and therefore not applicable to our subject population. Among the relatively newer diagnostic methods, genetic markers (32,(41)(42)(43)(44) and US elastography (33)(34)(35)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60) have been evaluated. A new molecular test, Afirma (Veracyte, South San Francisco, Calif) has shown promise for preoperative malignancy risk stratification for these nodules (32).…”
Section: Swe Findingsmentioning
confidence: 99%